Camaras pupales fósiles de coleópteros: el icnogénero Rebuffoichnus Roselli - Genise, Jorge Fernando (2002)
The ichnogenus Rebuffoichnus was created by Roselli in 1987 to include a single ichnospecies, R. casamiquelai. In this contribution, this ichnotaxon is redescribed and compared with similar trace fossils attributed to coleopterans based on the examination of the holotype using computerized tomography, and a large series of specimens collected recently from another locality of different age. Differences among Rebuffoichnus, Monesichnus, Teisseirei and particularly Fictovichnus, are analyzed based on the type of wall, chamber fillings, and chamber shape.